PSYCHOSOCIAL FUNCTIONING FEATURES IN PRIMARY CARE PATIENTS ACCORDING TO INVOLVING BY MEANS OF CONSCIOUSNESS WAR - Markov, Arthur (PSYCHOLOGICAL JOURNAL, 2016)
In recent years, Ukraine suffers from the hybrid war, the key point of which is psychological and information processing of the population through the use of techniques and methods consciousness war (CW) – "War of consciousness", one of the powerful factors of the destructive effect of which is the significant weakening of the psycho-social individuals barriers and social systems. Purpose is to investigate the features of psychosocial functioning as one of the most vulnerable to the defeat as a result of consciousness influences spheres of life, in patients primary care, depending on the involvement of the use of CW means. Contingent and methods. From the 393 patients somatic profile district clinics were selected 221 people with symptoms of psychological maladjustment. From the expression of passion to the TV viewing (TV), searching news on the Internet or reading periodicals surveyed were divided into two groups: the main group (MG) – 112 patients primary care with signs of bending psycho-emotional sphere and high involvement to the use consciousness effects through TV, internet or printed periodicals, and the comparison group (CG) – 109 patients with symptoms of psychological maladjustment to the low use of TV, online or print media CW. The survey was carried out by a clinical-psychological and psycho-diagnostic methods. Results. Individuals who have had a tense addictive status relatively to hobbies watching TV and using the Internet, with the result that they were vulnerable to the destructive effects of CW, demonstrated a pronounced deformation of psychosocial functioning, which was reflected in a high level of social and personal frustration, expressed by dissatisfaction with the functioning in all spheres of life, a high degree of social exclusion with the subjective feeling of loneliness, inadequacy and ambivalence of self-esteem and self-confidence, lack of or low ability to social empathy and a low capacity for social and psychological adaptation. Psychosocial functioning of patients the primary care with a low level of involvement to watching television and using the Internet, characterized by an average level of social and personal frustration, lower expression of feelings of loneliness and social isolation, low levels of self-esteem and self-confidence, however, high – social empathy that, in general, It formed the great potential of social and psychological adaptation. Conclusion. The results confirm the presence of the negative influence of the CW on the condition of mental health of the civilian population, which requires the development of psycho-correction activities and psycho-maladaptive states, due to the action of CW factors.